PENENTUAN MAHAR PERKAWINAN PERSPEKTIF IMAM SYAFI’I - Fahrul Fahroni; Fahmi Assulthoni; Mohsi Mohsi (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
In marriage there are definitely conditions, one of which is the dowry or dowry as a form of obligatory gift from a husband to his future wife. Of all the opinions of Madhhab Imams, only the opinion of Imam Syafi'i does not provide a minimum limit regarding dowry and also does not make it a marriage pillar, while other Madhhab Imams such as Imam Maliki, Imam Abu Hanifah and Kufa ulama provide a minimum limit for dowry that must be given to the bride and groom. Woman. Imam Maliki also made it harmonious in marriage. For this reason, researchers want to research it by formulating the problem as follows: 1). What is the concept of dowry position according to Imam Syafi'i 2). What is the concept of dowry payment according to Imam Syafi'i? To answer the questions above, the author uses the research method library research, meaning a study by examining books related to this thesis taken from the literature. All sources come from written materials related to the problems in the study and are also taken from other appropriate literature. From the discussion of this thesis, it can be concluded that, first, the concept of dowry position according to Imam Syafi'i is not a pillar of marriage, but is a condition for the validity of marriage. It is not obligatory to give a dowry to the wife if the husband divorces her before dukhu>l and has not determined the dowry. This means that if the wife has been interfered with, she is obliged to determine the dowry, that the dowry is not a pillar and condition of marriage, but is an obligation of the husband for sexual intercourse. Second, the concept of dowry payments according to Imam Syafi'i which allows the postponement of dowry payments which allows partial or complete postponement of dowry payments if the prospective wife agrees. explains that dowry payments can be made in cash directly at the marriage contract and can also be postponed if the bride and groom agree. The suspension of dowry payments can be done in part or in full according to the agreement with the bride and groom.